Obafemi Awolowo Political Theory: A Philosophical Critique. - Fasoro, Joseph Olurotimi (Obafemi Awolowo University, 2014)
A number of Scholars have argued that no African Politicians can be said to have formulated anything that can be regarded as a 'Political theory' that is worth academic study. This line of argument is often based on the inconsistent incoherent and sometimes eclectic nature of the political writings and utterances of African Political Leaders.